2008
DOI: 10.1088/0957-4484/19/10/105301
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Cd3As2nanowires by direct vapor–solid growth, and their infrared absorption properties

Abstract: In this work the authors introduce and provide details of the synthesis and spectral characterization of single-crystal nanowires in less common, high performance, group II-V semiconductors such as Cd(3)As(2). The growth mechanism critically deviates from a known vapor-liquid-solid one by being completely non-catalytic and involving only two states: vapor and solid. The resultant nanowires range from ∼50 to 200 nm in diameter and reach lengths up to tens of micrometers, with their fast growth direction being n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Till now, Cd 3 P 2 , Zn 3 P 2 , and Cd 3 As 2 among the II–V group semiconductors were found to be able to form into the nanowire structures. Omari et al [ 53 ] reported the synthesis of single-crystalline Cd 3 As 2 nanowires by thermal evaporation of Cd 3 As 2 powders at 750 °C. Figure 3 a is a SEM image of the Cd 3 As 2 nanowires.…”
Section: Typical 1-d Nanostructures Of Ii–v Group Semiconductorsmentioning
confidence: 99%
“…Till now, Cd 3 P 2 , Zn 3 P 2 , and Cd 3 As 2 among the II–V group semiconductors were found to be able to form into the nanowire structures. Omari et al [ 53 ] reported the synthesis of single-crystalline Cd 3 As 2 nanowires by thermal evaporation of Cd 3 As 2 powders at 750 °C. Figure 3 a is a SEM image of the Cd 3 As 2 nanowires.…”
Section: Typical 1-d Nanostructures Of Ii–v Group Semiconductorsmentioning
confidence: 99%
“…Omari et al reported the non-catalytic vapor-solid growth of Cd 3 As 2 nanowires from a Cd 3 As 2 film, ruling out any effect of Cd on the growth. 8 For Zn 3 As 2 , on the other hand, it is known that Zn particles act as self-catalysts in the vapor-liquid-solid growth of nanowires. 9 In this letter, we present the growth and structural analysis of Cd 3 As 2 micro-and nanowires by X-ray diffraction (XRD), Raman spectroscopy, atomic force microscopy (AFM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) with energy dispersive X-ray spectroscopy (EDS).…”
mentioning
confidence: 99%
“…The above analysis and characterization results indicate that single crystal mullite nanowires have been produced in large quantities. Since no catalyst, gaseous precursors, template, and surfactants are used, common mechanisms for nanowires such as vapor-liquid-solid growth, 28 vaporsolid growth 29 and template confined growth 30 cannot be employed to explain the formation process of these mullite nanowires. In our experiment, if we directly mix Al 2 O 3 s , SiO 2 s and Na 2 SO 4 s with the same molar ratio and heat the mixture to 1000 C for 3 h, mullite nanowires cannot be synthesized.…”
Section: Resultsmentioning
confidence: 99%